Sexual risk behaviors and STDs among persons who inject drugs: A national study - Brookmeyer, Kathryn A. (Prev Med, 2019)
Opioid use and the rising case reports of STDs represent co-occurring epidemics; research indicates that persons who inject drugs (PWID) may be at increased risk for acquiring STDs. We use the National Survey of Family Growth (NSFG, 2011–2015) to examine the prevalence of risky sexual behaviors and STD diagnoses among PWID. We describe demographic characteristics, sexual behaviors, and self-reported STD diagnoses of sexually active women and men, separately, by whether they had ever engaged in injection-related behaviors (age 15–44; N = 9006 women, N = 7210 men). Results indicate that in 2011–15, 1.4% of women and 2.6% of men reported ever engaging in injection-related behaviors. Examining the full logistic regression models indicate that for women, sex with a PWID in the past 12 months (AOR = 5.8, 95% CI: 2.9, 11.7), exchanging money/drugs for sex in the past 12 months (AOR = 3.6, 95% CI: 1.2, 10.9), chlamydia and/or gonorrhea diagnosis in the past 12 months (AOR = 2.6, 95% CI: 1.2, 5.3), ever having a syphilis diagnosis (AOR = 8.5, 95% CI: 3.1, 23.4), and ever having a herpes diagnosis (AOR = 3.3, 95% CI: 1.0, 10.3) were associated with increased odds of engaging in injection-related behaviors. For men, sex with a PWID in the past 12 months (AOR = 10.9, 95% CI: 4.3, 27.7), ever being diagnosed with syphilis (AOR = 5.8, 95% CI: 1.8, 18.0), and ever being diagnosed with herpes (AOR = 2.7, 95% CI: 1.0, 7.1) were significantly associated with increased odds of engaging in injection-related behaviors. Future research may examine critical intervention points, including co-occurring factors in both STD acquisition and injection drug use.